Ruina montium - Paden, Jeremy (Colección de poesía (Valparaíso Ediciones) ;, 2018)
"Poetry. Latino/Latina Studies. For sixty-nine days in 2010 the world held its collective breath while thirty-three men were trapped deep in a copper mine in Chile. The story of their survival and rescue is by now well-known, but through the poetry and imagination of Jeremy Paden the intimate humanity of this modern-day resurrection is rendered with exquisite feeling for the miners below and their loved ones above. Many of the individual miners appear here in poems inspired by their specific stories. But as suggested by the title, (a term coined by Pliny to describe Roman hydraulic gold mining and its effect on the land) this is also a meditation on our relationship to our planet." From original English edition, Broadstone Books.